Better off dead - Child, Lee; Child, Andrew, 1968- (Delacorte Press, 2021)
"Jack Reacher is back in the brand-new, page-turning thriller from acclaimed #1 bestselling authors Lee Child and Andrew Child. Reacher isn't one to back down from a fight. And when a shadowy crew raises the stakes, he won't hesitate to teach them a lesson: When you pick a fight with Reacher, you're better off dead"--
Keywords: Reacher, Jack -- (Fictitious character) -- Fiction; Mystery fiction; Suspense fiction; Thrillers (Fiction); Novels